A produção do território e da moradia e da moradia no quilombo Bom Jardim da Prata - Amaro Sérgio Marques (2018)
The rural area of the municipality of São Francisco, north of Minas Gerais, between the Acari and Pardo rivers, from the period of colonization, served as a refuge and resistance to the slave system with the formation of the quilombo Bom Jardim da Prata. The present work hopes to analyze the process of formation of this quilombola community, as well as the production of space, housing and its territorialities. For this purpose, the ethnographic and oral history method was used to collect data with the residents of the community. At present there are no statistical data on this community, but it is estimated that there are 630 families living in small dispersed sites or in three denser villages in the territory. Nonetheless, there were always other Negroes as well, such as Indians and whites, who traveled throughout this region and founded, from the earliest farms to cattle and urban centers. However, from the 1950s, new economic arrangements changed the way of appropriation of the territory, generating new territorialities, mainly with the process of enclosure promoted by the great landowners. Some of the former residents of the quilombo stayed in the midst of large and medium-sized farms, often unable to continue to use areas formerly occupied collectively by their ancestors. Many residents then had to work for the region's large farmers or undergo seasonal work in other cities as a way to improve their income. In this kind of fragmented territory, which was being formed, we have the presence of quilombolas and nonquilombolas, farmers, besiegers, rural workers, gypsies, all living in the same area. However, in the last decade, the quilombola association of Bom Jardim da Prata is claiming the titling of its lands, which, in fact, would be occupied by several non-quilombola residents. Thus, if approved, a new collective territory with more than 63,000 hectares will be created to be managed by the Quilombola Association of Bom Jardim da Prata. However, the fate of other non-Quilombola residents in the disputed territory is not yet clear. It is also possible to question the community character in this territory, since its inhabitants seem little cohesive and many of them indifferent to the quilombola question. In recent years, new external processes have once again impacted this region, from the possibility of building the bridge over the São Francisco River and the arrival of the National Rural Housing Program (PNHR), all of these elements of the new economic, territorial and social relations. It is true that each year the quilombo residents seem to be less autonomous, since they seem to live with total dependence on public policies and external agents. I see, therefore, a long process of struggle for the consolidation of the community and the territory, that yes, essential for the reproduction, maintenance and resignification of the quilombo.